Features improvement techniques supply of highly skilled bodybuilders in transition training - Oleksandr Aghyppo (Kharkiv State Academy of Physical Culture, 2015)
Purpose of this paper is to improve the supply of highly skilled technique bodybuilders training in a transition period with the restoration of lean body mass and functional state of an athlete after a competitive activity. Material and Method: the study involved 18 highly skilled bodybuilders are included in the team of the Kharkiv region of Ukraine and bodybuilding. Results: a comparative characteristic of the conventional technique that is often used in the training process in bodybuilding. Developed and justified the optimal technique for highly skilled bodybuilders, depending on the initial form of the athlete at the beginning of the transition period of training. Conclusions: on the basis of the study the author suggests best practices in supply depending on the microcycle training in transition training.